b - Sen, Promode Kumar; Sen, Prasenjit (trans.). (b, 2018)
Sri Aurobindo was a scholar, a literary critic, a philosopher, a revolutionary, a poet and a yogi. He became a leader of India's fight for independence and later a well-known spiritual guru. The original version of this book was written at a time when any writing on Sri Aurobindo was frowned upon by the British government. It is not only a biography of the spiritual leader but also an analysis of the Congress party during the Independence movement, the split in Surat Congress, as well as the spiritual practice developed by Sri Aurobindo known as Spiritual Yoga.
Keywords: Philosophers -- Biography. -- India; Nationalists -- Biography. -- India; Yogis -- Biography. -- India